Traditional Beliefs And Practices During Postpartum Amongst Malay Women - Jane, Buncuan; Siti Fatimah, Binti Salleh (2018)
Introduction: Postpartum period is a critical adjustment period for woman and her newborn physiologically, emotionally and socially. It is a time when the woman’s behaviour could be influenced by their cultural background. Aim: This study aimed to explore the traditional beliefs and practices during postpartum among the Malay women. Method: A descriptive qualitative study was conducted in Sungai Petai, Malacca. The participants were selected by using a purposive sampling. In-depth interviews were used. Data collected were analysed manually. Saturation was reached at the ninth participant. Findings: The findings revealed that (1) Malay women believed the confinement period as a healing period after delivery, (2) they were kotor (dirty) after delivery, and (3) they believed that they are susceptible to bentan (getting ill) and (4) meroyan (postpartum psychosis). Most of the participants strictly abide by the traditional practices. Conclusion: This study showed that postpartum mothers practised traditional beliefs during their confinement. It is suggested to do further studies which involve different ethnic groups and different settings.